(untitled) (Damascus University Journal for engineering sciences, 2021)
The research is about improving the reliability of the computer as an essential element of monitoring and control of an electric power station (or operating room - intensive care units in hospitals) and other similar applications. The research focuses on the development of the Online Diagnostic algorithm to implement in personal computer (PC) , to shorten (MTTR) mean time to repair and increase computer availability as a reliability indicator by quickly detecting software errors and hardware Failure . The research also deals with the design of a technical tool (diagnostic model) in the form of a microcomputer from a single card, so that it can be connected to the computer through the programmable ports to run the online diagnostic algorithm and other important software in case of a sudden computer failure.